A history of medieval philosophy - Copleston, Frederick C. (Frederick Charles), 1907-1994. (Notre Dame, Ind. : University of Notre Dame Press, 1990)
Explores the nature of medieval philosophy and its place in the development of Western thought.
First published: New York : Harper & Row, 1972.
Bibliography: p. [347]-381.
Keywords: Philosophy, Medieval